Problems of development and current state of marketing in the tourism industry of the Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
Article marketing has been considered the activities of state and local authorities in the sphere of tourism of the Republic of Kazakhstan and problems of development in the present stage, as well as the main types of services offered by domestic tour operators.